EXPLORING ENGLISH LEARNING EXPERIENCES: ENJOYMENT AND ANXIETY AMONG RURAL JUNIOR HIGH STUDENTS - listiani, Eva; Sutrisno, Djoko (IKIP Siliwangi, 2024)
This research examines the enjoyment and anxiety of learning English experienced by junior high school students in rural areas. This research uses quantitative methods, with data collection using a questionnaire distributed to 54 class VIII students. The findings show that a positive classroom environment and a friendly teacher who always provides support can increase students' enjoyment in learning English. On the other hand, student anxiety stems from self-doubt about their abilities and fear of negative evaluation. Statistical analysis, including independent sample t test, revealed significant differences between levels of enjoyment and anxiety. This makes teachers implement teaching strategies that can reduce anxiety, such as providing emotional support and using varied teaching methods. This study focuses on understanding emotional factors in language learning and provides practical recommendations for improving the quality of education in school environments, especially in rural areas.